Concetti mentali e pubblicità: in difesa del soggettivismo - Zonca, Joshua (Rivista Italiana di Filosofia del Linguaggio, 1970)
The debate about the ontology of concepts is characterized by a marked contrast between objectivism and subjectivism. According to the first approach, concepts are abstract and universal entities, whose existence is independent of our minds. Subjectivists, on the contrary, consider concepts as mental objects, which are directly involved in our cognitive processes. In this paper, I discuss one of the mostrelevant arguments by which objectivists try to discredit the subjectivist approach, the one offered by Frege about the non-shareabilty of mental concepts. In particular, I make use of the issues raised by Glock (2009), who has utilized the fregean argument to demonstrate that subjectivists, including Fodor and Margolis and Laurence, cannot maintain that concepts seen as mental objects are shareable between individuals, since shareability can be satisfied only by abstract and universal entities. On the contrary, I show that the subjectivist approach can withstand this attack and affirm that mental concepts are shareable, in the sense that they can guarantee communication. On one hand, Fodor, as well as Margolis and Laurence, is right to consider as sufficient, in order to satisfy the requirement of shareability, a notion of identity between tokens of mental representations; on the other hand, subjectivists can easily make use of a notion of convergence to guarantee the shareability of concepts and, consequently, successful communication. The last section of the article argues, against Glock, that concepts can be mental representations.